CAPITAL CAPABILITY ANALYSIS OF COFFEE BUSINESS (Case Study: Sitolu Bahal Village, Lintongnihuta District, Humbang Hasundutan Regency) - Trisya Hongsiana Nainggolan (Institute of Computer Science (IOCS), 2020)
This study aims to analyze the social and economic characteristics of coffee farmers, the annual capital requirements of each coffee farmer, methods and sources of capital procurement for coffee farmers, the amount of allocation of funds received by farmers from their income for further farming capital, as well as the role of the government in strengthening the capital of coffee farmers in Indonesia. research areas. The results showed that the social characteristics of the farmers, namely the average education condition of the sample farmers was 11 years, the tenure / status of farmer's land ownership of their own land, family inherited land, profit sharing land and leased land, farmers ' openness to access to capital was 29, 30% choose to borrow from formal institutions, namely banks and CUs and 13.80% choose to borrow from non-formal institutions, namely family or fellow farmers, and economic characteristics, namely the total income of farmers are IDR 18,526,254 per year; The capital requirements needed by farmers in conducting coffee farming are IDR 3,017,170 per year; The method and source of farmers' capital procurement come from their own capital by 56.90%, from CU 27.60%, from friends/fellow farmers by 10.35%, from toke by 3. 45% and from banks by 1.72% from the total of all samples; Sample farmers can allocate as much as 39.2% of their income for further farming capital; The government's role in strengthening capital in Desa Sitolu Bahal is only in the form of fertilizer subsidies which are channeled through official fertilizer kiosks and farmer groups at prices that are cheaper than non-subsidized fertilizers.